Diversión : Play and Popular Culture in Cuban America - Laguna, Albert Sergio (Book collections on Project MUSE., 2017)
In an era of warming relations between the US and Cuba, this book updates the conversation about Cuban America by revealing how this community has changed over the past 25 years. Albert Sergio Laguna investigates the generational shifts and tensions in a Cuban America where the majority is now made up of those who have arrived since the 1990s and those born in the US. To probe these changes, Laguna examines the aesthetic and social logics of a wide range of popular culture forms originating in Miami and Cuba from the 1970s through the 2010s. They include the stand-up comedy of performers like Alvarez Guedes, festivals, a media distribution network in Cuba called el paquete, morning radio shows, and the viral content of Los Pichy Boys, among others. This study illustrates the centrality of play in a community that has been described historically as angry and melancholic. Diversión contends that our understanding of the Cuban diaspora is lacking not in seriousness, but in play. By unpacking this archive, Laguna explores our complex, often-fraught attachments to popular culture and the way it can challenge and reproduce normative cultural ideologies-especially in relation to politics and race. In the wake of the largest Cuban migration wave to the US in history, Diversión is crucial reading for those who seek to understand not only the Cuban. American diaspora, but cultural and economic life on the island. Book jacket.